Indeks Zero Waste Ruang Terbuka Hijau di Sleman dan Panduan Optimalisasi - Dian Ferdiansyah; Arif Kusumawanto; Sri Puji Saraswati (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research is part of an effort to solve waste management issues in Sleman Regency, focusing on measuring and evaluating the Zero Waste Index (ZWI) in the Green Open Space (RTH) Denggung, Sleman. The resource substitution method was used to assess the efficiency and potential for waste reduction in the area. Based on field data and calculations using the ZWI formula, it was found that the ZWI value in RTH Denggung is very low, only 0.14, meaning that only about 14% of resources are recovered from the waste management system. This indicates that waste management in the area is not yet optimal, necessitating improvement and innovation efforts. The proposed strategies include enhancing the recycling of plastic, paper, and styrofoam waste, as well as developing composting for food scraps and other organic waste. The implementation of stricter policies related to waste management, public awareness campaigns, and the integration of zero waste initiatives are expected to improve the ZWI value. This effort is hoped to be part of the solution to waste management in Indonesia and serve as a best practice example for waste management in RTH or other public spaces..